Experimental study on basic mechanical properties of lightweight self-insulation concrete block masonry in Northeast cold region - Bashir H. Osman; Zhongfan Chen; Abu-Bakre A. Elamin (Scientific Reports)
Abstract In this paper, mechanical and thermal properties of block type are optimized to ensure a more reasonable stress distribution for the self-insulating block. Based on the mix - ratios provided by the standards and considering the technical conditions of the production process, 16 sets of orthogonal experiments are designed to investigate the effects of sand content, water-cement ratio, and the density of the concrete matrix material on the compressive strength of vibrated and pressed expanded clay concrete. Furthermore, basalt rock wool is used as an additive to improve the mix ratio to meet the material requirements of the optimal block type, then, a new composite self-insulating concrete block is developed. Through mechanical performance tests of the blocks, the effects of the vibration-pressing molding process and the composition of the expanded clay lightweight aggregate on the strength development of the new composite self-insulating concrete block are investigated. Additionally, a relationship formula is fitted to describe the development of compressive strength with age. The results showed that the design compressive strength values of the new block masonry are higher than the strength of the “double-row or multi-row hollow lightweight aggregate concrete block masonry with a MU5.0 + Mb5.0 grade,” making it suitable for use in two-story masonry load-bearing walls in rural buildings in the cold northeastern regions. Moreover, comparative analysis shows that the average compressive strength value provided by the standards for concrete block masonry is applicable to the new composite self-insulating concrete block masonry. The shear strength of the new block masonry along the mortar joint cross-section shows a significant increase compared to the shear strength values specified in the standards for ordinary concrete hollow block masonry. Finally, proposed equation is recommended to calculate the compressive stress-strain curve, which shows suitable results for the new block masonry.